2014
DOI: 10.1016/j.cell.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Focusing in on T Cell Cross-Reactivity

Abstract: To provide broad immunity to a vast array of foreign antigens with a limited number of T lymphocytes, each cell has to recognize many targets. By implementing a strategy to identify T cell receptor (TCR) ligands and investigating at a fine granularity their structure and sequence relationship, Birnbaum et al. demonstrate the surprisingly tight focus of such T cell cross-reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Thus, the TCR-repertoire has been termed unlimited. However, the relation between the possibility of recombination of the TCR and the number of universally possible peptides implies an imperative TCR promiscuity: 10 11 human TCRs have to match with 10 20 peptides [73] (Fig. 3).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the TCR-repertoire has been termed unlimited. However, the relation between the possibility of recombination of the TCR and the number of universally possible peptides implies an imperative TCR promiscuity: 10 11 human TCRs have to match with 10 20 peptides [73] (Fig. 3).…”
Section: Reviewmentioning
confidence: 99%
“…Hence, a necessary feature of a TCR repertoire is that a T-cell is able to recognize and respond to many peptides, but one TCR only recognizes and responds to peptides closely related to the original agonist peptide (similar colors representing peptide relatedness). Modified from Mandl and Germain 2014 [73]…”
Section: Reviewmentioning
confidence: 99%
“…Considering that most documented cases of T-cell off-target toxicity have been associated with molecular mimicry ( 20 , 21 , 52 , 70 ), we expected that validated target/off-target pairs should in general present low relatedness scores. In this context, the relatedness distribution obtained in the Monte Carlo simulation described in section 4.3 can both be used to understand the dispersion of validated cases, and to identify confidence boundaries in our predictions (i.e., statistical threshold).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, engineering a T-cell receptor is a challenging task that involves potentially conflicting goals, such as enhancing the T-cell response to the tumor-derived peptide, while avoiding side effects caused by T-cell cross-reactivity (16)(17)(18). T-cell cross-reactivity is the ability of a single T-cell clonotype to recognize and respond to multiple heterologous peptide-HLA (pHLA) complexes (19)(20)(21). From an evolutionary perspective, T-cell cross-reactivity is necessary to maximize the range of unrelated antigens/pathogens that can be recognized by a limited pool of T-cells (i.e., to mediate heterologous immunity between pathogens) (22-24).…”
Section: Introductionmentioning
confidence: 99%
“…However, T cell cross-reactivity is not determined only by sequence similarity. Recent studies have demonstrated that T cell cross-reactivity is also determined by structural similarities of unrelated peptide-HLA (pHLA) complexes (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%